Appuyer les organisations de producteurs - Dugué, Marie-Jo (éditions Quae, 2012)
Producer organisations are very numerous and active in the farming modernisation process in southern developing countries. This didactic work analyses the advantage of the partnership with producer organisations, how they can be strengthened and their relations with the environment. The questions are made extremely accessible and are illustrated by numerous examples in the southern countries.